i want to add a loop so that it works like this.

조회 수: 1 (최근 30일)
SAHIL SAHOO 2022년 10월 10일
댓글: SAHIL SAHOO 2022년 10월 11일
ti = 0;
tf = 1E-3;
tspan=[ti tf];
KC = 4E-3;
y0= [ (10e-6)*rand(2,1); ((-3.14).*rand(1,1) + (3.14).*rand(1,1));
(10e-6)*rand(2,1); ((-3.14).*rand(1,1) + (3.14).*rand(1,1));
(10e-6)*rand(2,1); ((-3.14).*rand(1,1) + (3.14).*rand(1,1));
(10e-6)*rand(2,1); ((-3.14).*rand(1,1) + (3.14).*rand(1,1));
(10e-6)*rand(2,1); ((-3.14).*rand(1,1) + (3.14).*rand(1,1));
((-3.14).*rand(5,1) + (3.14).*rand(5,1))];
yita_mn = [
0 1 0 0 1;
1 0 1 0 0;
0 1 0 1 0;
0 0 1 0 1;
1 0 0 1 0;
N = 5;
t = 1E-3;
[T,Y]= ode45(@(t,y) rate_eq(t,y,yita_mn,N),tspan,y0);
hold on
for m = 16:20
hold off
grid on
ylabel("phase difference")
set(gca,'fontname','times New Roman','fontsize',18,'linewidth',1.8);
function dy = rate_eq(t,y,yita_mn,N,o)
dy = zeros(4*N,1);
dGdt = zeros(N,1);
dAdt = zeros(N,1);
dOdt = zeros(N,1);
P = 0.05;
a = 5;
T = 2E3;
Gt = y(1:3:3*N-2);
At = y(2:3:3*N-1);
Ot = y(3:3:3*N-0);
k = 4E-3;
for i = 1:N
dGdt(i) = (P - Gt(i) - (1 + 2.*Gt(i)).*(At(i))^2)./T ;
dAdt(i) = (Gt(i).*(At(i)));
dOdt(i) = -a.*(Gt(i));
for j = 1:N
dAdt(i) = dAdt(i)+yita_mn(i,j).*(At(j))*sin(Ot(j)-Ot(i));
dOdt(i) = dOdt(i)+yita_mn(i,j).*((At(j)/At(i)))*cos(Ot(j)-Ot(i));
n1 = (1:5)';
n2 = circshift(n1,-1);
n16 = n1 + 15;
n17 = circshift(n16,-1);
n20 = circshift(n16,1);
j2 = 3*(1:5)-1;
j5 = circshift(j2,-1);
j8 = circshift(j2,-2);
j19 = circshift(j2,1);
%%%%%%%%%%%%%%%%%%%%%%%%%%% here i wanted to add a loop so that when
% Gt(i) = Gt(1) then the Gt(i+1) = 2 and when the Gt(i) = Gt(5) then the Gt(i+1) = Gt(1)
%i dont know how to addd this loop pelase help me in it.
dy(n16) = -a.*(Gt(i+1) -Gt(i)) - (k).*(y(j2)./y(j5)).*sin(y(n16)) - (k).*(y( j5)./y(j2)).*sin(y(n16)) + (k).*(y(j8)./y(j5)).*sin(y(n17)) + (k).*(y(j19)./y(j2)).*sin(y(n20));
dy(1:3:3*N-2) = dGdt;
dy(2:3:3*N-1) = dAdt;
dy(3:3:3*N-0) = dOdt;

답변 (1개)

Jeffrey Clark
Jeffrey Clark 2022년 10월 10일
편집: Jeffrey Clark 2022년 10월 10일
@SAHIL SAHOO, since Gt(1) is not changed after the initial setting from the y input, and Gt(i+1) is not refereced before where you say you want to change Gt(i+1), you can just set Gt(2:end) before the i loop:
Gt = y(1:3:3*N-2);
% Gt(i) = Gt(1) then the Gt(i+1) = 2 and when the Gt(i) = Gt(5) then the Gt(i+1) = Gt(1)
Gt([false Gt(1:end-1)==Gt(1)]) = 2;
Gt([false Gt(1:end-1)==Gt(5)]) = Gt(1);
  댓글 수: 3
Jeffrey Clark
Jeffrey Clark 2022년 10월 11일
@SAHIL SAHOO, you askeda very specific question which is what I answered and showed the two lines added just after where Gt is defined. I suspect you are asking the more general question as to why you aren't getting the results you want? Please check that the code you pasted in your initial post is what you are running, when I reformatted it slightly and without adding my two lines the code debugger points out that the parameters for the call to rate_eq don't match the functions', and the function doesn't use its first or last parameter t and o (see attached your reformatted code). It is also unlikely that Gt(i) would ever be exactly the same as Gt(1) or Gt(5) since they are random numbers:
[T,Y]= ode45(@(t,y) rate_eq(t,y,yita_mn,N),tspan,y0);
function dy = rate_eq(t,y,yita_mn,N,o)
SAHIL SAHOO 2022년 10월 11일
i get coreect solution by using the n

댓글을 달려면 로그인하십시오.


Help CenterFile Exchange에서 Loops and Conditional Statements에 대해 자세히 알아보기


Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by